Deutschland und die "Wende" in Literatur, Sprache und Medien - Interkulturelle und kulturkontrastive Perspektiven Dokumentation eines Expertenseminars für internationale Alumni der Georg-August-Universität Göttingen vom 8. - 13. Juli 2007 - Casper-Hehne, Hiltraud; Schweiger, Irmy (Universitätsverlag Göttingen, 2008)
With its expert seminars for alumnis abroad the Georg-August-University Göttingen wants to strengthen its contact with the alumni in the long term and create a global network. This volume is the result of a seminar on "Germany and the Wende (Change) in Literature, Language and Media". The participants were scientists, writers and filmmakers with their own views on contemporary German history and the reunification as well as alumni from China, Japan and Korea who are involved in their home countries in the dissemination of German language and culture. The seminar and the title discuss a specifically German experience, the reunification ("Die Wende") as central theme which also has an actual and high relevance in Korea and China.